Risk Behavior Assessment Jemaah Makassar dalam Pencegahan Travel Disease Saat Umroh - Harpiana Rahman; Rizki Aulia Yusuf; Septiyanti Septiyanti (FORIKES, 2024)
Qualitative study through interviews with congregants from Makassar who had symptoms of illness such as sore throat, fever, cough, flu, and congregants who did not have symptoms of illness admitted that they were not intensive in using masks even though they were in a crowd of congregants. Healthy behavior is an important and effective practice that the congregation can carry out in controlling travel disease pathogens when performing the Umrah pilgrimage. So research is needed that aims to examine the behavior of tourists or Umrah pilgrims during their pilgrimage and assess behavior at risk of contracting travel disease. This research was conducted using quantitative methods. The research subjects were 66 respondents who had just returned from the Umrah pilgrimage, who were selected using a simple random sampling technique. Measurement of risk behavior was measured using the Preventive Measures for Hajj-Associated Health Risks instrument with modifications. Data were analyzed using descriptive statistical methods. The results showed that high level risk behavior = 32.4%, medium level = 64.7% and low level = 2.9%. It was concluded that the majority of Umrah pilgrims behaved at a moderate level of risk.Keywords: risk behavior; Umrah congregation; travel sickness ABSTRAK Studi kualitatif melalui wawancara dengan jemaah dari Makassar yang mendapatkan gejala penyakit seperti sakit tenggorokan, demam, batuk, flu, dan kepada jemaah yang tidak mendapatkan gejala sakit mengakui tidak intens dalam menggunakan masker meski berada dalam kerumunan jemaah. Perilaku sehat menjadi amalan penting dan efektif yang bisa dilakukan jemaah dalam mengendalikan patogen travel disease saat melakukan ibadah umroh. Sehingga diperlukan penelitian yang bertujuan untuk mengkaji perilaku wisatawan atau jemaah umroh selama melaksanakan ibadah dan menilai perilaku beresiko tertular travel disease. Penelitian ini dilakukan dengan metode kuantitatif. Subyek penelitian adalah 66 responden yang baru saja pulang dari ibadah umroh, yang dipilih dengan teknik simple random sampling. Pengukuran perilaku beresiko diukur dengan instrumen Preventive Measures for Hajj-Associated Health Risks dengan modifikasi. Data dianalisis dengan metode statistika deskriptif. Hasil penelitian menunjukkan bahwa perilaku berisiko tingkat tinggi = 32,4%, tingkat sedang = 64,7% dan tingkat rendah = 2,9%. Disimpulkan bahwa sebagian besar jemaah umroh berperilaku berisiko dalam tingkat sedang.Kata kunci: perilaku berisiko; jemaah umroh; travel disease